(827) A Note in Development Planning and the Role of Enterprise مذكرة في التخطيط الإنمائي ودور المؤسسات في التنمية - Penrose, E. (معهد التخطيط القومى, 2024)
The study addresses one of the major challenges for state policies in formulating plans to promote economic development and control the economy, specifically the role of the enterprise (the firm) in economic life. This issue is particularly evident outside the agricultural sector, where the failures of central planning in socialist economies have become increasingly apparent in recent years. The study highlights that changes in the economic management of these economies have largely resulted from the failure of earlier conceptions regarding the relationship between the enterprise and the economic plan. It emphasizes the importance of re-evaluating this relationship to achieve more balanced and sustainable economic success.